The surgical correction of presbyopia - Gierek-Ciaciura, Stanisława; Wyględowska-Promieńska, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
There are a lot of surgical procedures to correct refractive errors, but the surgical correction of presbyopia is still a problem. In this paper the authors present surgical procedures, which can be used to correct presbyopia. There are three groups of surgery: the corneal, scleral and intrabulbar procedures.